Rational Thinking In Love And Islamic Concept Of Love: A Preventive Strategy For Youth Mental Health Issues - Syaidatun Nazirah Abu Zahrin; Rezki Perdani Sawai; Joki Perdani Sawai; Mohd Azman Abas (Universiti Putra Malaysia Press, 2026)
Non-Indexed Publication